(untitled) (Culturas Científicas, 2022)
A vision of epistemology is presented as a logic of thinking and it is taken to an elaboration of clinical practice as a logic of mental illness. This proposal is based on the approaches of Deleuze and Guattari to mental illness and to literature. As well, we will take as a starting point the notion of aberrant movements, elaborated by David Lapoujade when he reads Deleuze’s work. These movements will be understood as those that occur in the relationship between different heterogeneous terms, when their heterogeneity is maintained. This is linked to the invitation that Lapoujade himself makes to understand Deleuze’s work as the development of irrational logics. We will try to think, from there, a logic of madness and mental illness based, in turn, on a logic of the literary works of Proust and Kafka, as read by Deleuze and Guattari themselves. In relation to this, we highlight, on the one hand, a certain logic of open and non-totalizable sets, that these last authors find in Proust’s work and, on the other hand, a logic of contiguity that they find in Kafka’s work. At the same time, common points are established between these two readings, regarding the schizoid as something that exceeds the meaning in discourse, as well as the normativity of behavior. Likewise, at different points in the paper, we will deduce the implications that these ways of thinking have for a clinical practice in relation to subjective modes of existence that escape what is established in the social field. In that way, we join an epistemological approach with a political one.